Storytelling increases oxytocin and positive emotions and decreases cortisol and pain in hospitalized children - Brockington, Guilherme (2021)
Storytelling is a distinctive human characteristic that may have played a fundamental role in humans' ability to bond and navigate challenging social settings throughout our evolution. However, the potential impact of storytelling on regulating physiological and psychological functions has received little attention. We investigated whether listening to narratives from a storyteller can provide beneficial effects for children admitted to intensive care units. Biomarkers (oxytocin and cortisol), pain scores, and psycholinguistic associations were collected immediately before and after storytelling and an active control intervention (solving riddles that also involved social interaction but lacked the immersive narrative aspect). Compared with the control group, children in the storytelling group showed a marked increase in oxytocin combined with a decrease in cortisol in saliva after the 30-min intervention. They also reported less pain and used more positive lexical markers when describing their time in hospital. Our findings provide a psychophysiological basis for the short-term benefits of storytelling and suggest that a simple and inexpensive intervention may help alleviate the physical and psychological pain of hospitalized children on the day of the intervention.